Coastal infrastructure and climate change adaptation in Bangladesh: Ecosystem services insights from an integrated SES-DAPSIR framework - Md Monzer Hossain Sarker; Alberto Gabino Martinez-Hernandez; Jesús Reyes Vásquez; Perla Rivadeneyra; Sebastian Raimondo (Fondazione Eni Enrico Mattei (FEEM), 2024)
The escalating impacts of climate change on coastal regions stress the urgency for effective adaptation strategies, particularly for the case of high-risk countries such as Bangladesh. Naturebased solutions, grey and mixed coastal infrastructure offer promising solutions for addressing these challenges. Prior publications have utilized decision-making models such as the DPSIR framework to explore the link between coastal infrastructure and climate change. However, until now none of them have used it in combination with broader frameworks. Moreover, few works have analyzed the south central coast of Bangladesh by following an integrated approach. Hence, this working paper aims to bridge these gaps by employing an integrated SES-DAPSIR framework to evaluate the main benefits and challenges provided by different types of coastal infrastructure, with a particular emphasis on ecosystem services. Our methodology involves a two-step approach. Firstly, we consolidated a structured questionnaire and conducted surveys within three different locations to gather community's perspectives on coastal infrastructure. Secondly, we developed an integrated SES-DAPSIR conceptual model, engaging scientific and policymaking stakeholders through an international workshop co-organized with FEEM, Universita' Ca' Foscari, and Murdoch University. The main results highlight the potential ecological impacts and costs associated with grey infrastructure, advocating for a balanced approach that combines green and grey solutions. Mixed solutions, integrating elements of both nature-based and grey infrastructure, show promise for optimizing adaptation efforts while minimizing ecological harm and cost. As part of this process, government leadership and international cooperation are deemed essential for driving public engagement and fostering societal resilience.
Keywords: Q50; Q54; Q57; Q58; 330; Climate change adaptation; coastal infrastructure; nature-based solutions; ecosystem services; integrated frameworks